Spatial Analysis of Comparison of Divorce Rates before, during COVID-19 Pandemic, and New Normal in Bandung City - Birawa, Arbian Sukma; Hadibasyir, Hamim Zaky (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Divorce is a social phenomenon that significantly impacts society, especially in an urban context such as Bandung City. This study aims to conduct a spatial analysis of the divorce rate in Bandung City before the COVID-19 pandemic, during the pandemic, and the new normal period. Methodology: This research method uses divorce rate data from the Bandung City Religious Court. The data was spatially analyzed using ArcGIS software to determine patterns and changes in the divorce rate in the city of Bandung during the pre-pandemic to the New Normal period. Results: The result of this study is that the divorce rate in Bandung City from 2019 to 2022 has increased, for several reasons including economic problems, conflicts and quarrels, neglect from one of the individuals, violence in the family environment, drunkenness, changes in religious beliefs, polygamy, imprisonment, gambling practices, use of illegal substances, physical limitations, forced marriage, and acts of infidelity.